2015
DOI: 10.1517/17425255.2015.1047341
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnicity on response to asthma drugs

Abstract: Health-care professionals might never use the treatment in their patients irrespective of their ethnicity and thus inadvertently increase ethnic health inequality. However, our understanding of whether and/or how ethnicity influences pharmacological response to asthma therapeutics is still very scarce. A holistic, integrative systems biology approach that combines large-scale molecular profiling traits (e.g., transcriptomic, proteomic, metabolomic traits) and genetic variants could help to personalize the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The "Asthma Inequality" is a well-known example showing the exacerbation in health disparity driven by missing minority subjects in research (Burchard, 2014;Cazzola et al, 2015). 21 Inhaled β2-agonists (such as Albuterol) are a widely used therapeutic drug for acute asthma.…”
Section: B Missing Diversity and Health Equity In The Era Of Genomic ...mentioning
confidence: 99%
“…The "Asthma Inequality" is a well-known example showing the exacerbation in health disparity driven by missing minority subjects in research (Burchard, 2014;Cazzola et al, 2015). 21 Inhaled β2-agonists (such as Albuterol) are a widely used therapeutic drug for acute asthma.…”
Section: B Missing Diversity and Health Equity In The Era Of Genomic ...mentioning
confidence: 99%
“…African‐American and Puerto Rican children also have a higher rate of asthma prevalence, mortality, and a lower drug response compared with Caucasians (Mak et al, ). This is of concern as, despite having more severe asthma, Puerto Rican children have a lower bronchodilator response to Albuterol, the most common drug prescribed for asthma exacerbations in children, compared with African‐American and Mexican children (Cazzola, Rogliani, Sanduzzi, & Matera, ). It is suggested that genetic variations contribute to the lower response to albuterol in Puerto Ricans and that genetics may also account for altered steroid responsiveness in African‐Americans with asthma (Cazzola et al, ).…”
Section: Vulnerability Factorsmentioning
confidence: 99%
“…This is of concern as, despite having more severe asthma, Puerto Rican children have a lower bronchodilator response to Albuterol, the most common drug prescribed for asthma exacerbations in children, compared with African‐American and Mexican children (Cazzola, Rogliani, Sanduzzi, & Matera, ). It is suggested that genetic variations contribute to the lower response to albuterol in Puerto Ricans and that genetics may also account for altered steroid responsiveness in African‐Americans with asthma (Cazzola et al, ). Researchers have also suggested that there is a variation in the PTCHD3 gene in African‐Americans that places them at a greater risk for developing asthma (White et al, ).…”
Section: Vulnerability Factorsmentioning
confidence: 99%
“…9 A 28-week safety extension of these studies (PINNACLE-3; NCT01970878) confirmed the long-term safety and efficacy of GFF MDI. 10 As patients of different ethnicities can respond differently to pharmacological therapies, 11,12 it is important to assess the efficacy and safety of new treatments in a range of patients from different geographical locations and ethnic backgrounds. The PINNACLE-4 study (NCT02343458) evaluated the efficacy and safety of GFF MDI in a geographically expanded population, which included patients from Asia, Europe, and the USA.…”
Section: Introductionmentioning
confidence: 99%